Genome-Wide Mapping of Targets of Maize Histone Deacetylase HDA101 Reveals Its Function and Regulatory Mechanism during Seed Development - Yang, Hua (Plant Cell, 2016)
Histone deacetylases (HDACs) regulate histone acetylation levels by removing the acetyl group from lysine residues. The maize (Zea mays) HDAC HDA101 influences several aspects of development, including kernel size; however, the molecular mechanism by which HDA101 affects kernel development remains unknown. In this study, we find that HDA101 regulates the expression of transfer cell-specific genes, suggesting that their misregulation may be associated with the defects in differentiation of endosperm transfer cells and smaller kernels observed in hda101 mutants. To investigate HDA101 function during the early stages of seed development, we performed genome-wide mapping of HDA101 binding sites. We observed that, like mammalian HDACs, HDA101 mainly targets highly and intermediately expressed genes. Although loss of HDA101 can induce histone hyperacetylation of its direct targets, this often does not involve variation in transcript levels. A small subset of inactive genes that must be negatively regulated during kernel development is also targeted by HDA101 and its loss leads to hyperacetylation and increased expression of these inactive genes. Finally, we report that HDA101 interacts with members of different chromatin remodeling complexes, such as NFC103/MSI1 and SNL1/SIN3-like protein corepressors. Taken together, our results reveal a complex genetic network regulated by HDA101 during seed development and provide insight into the different mechanisms of HDA101-mediated regulation of transcriptionally active and inactive genes.